KOMPETENSI PEDAGOGIK GURU MENERAPKAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN BIOLOGI DI MADRASAH ALIYAH NEGERI 2 MODEL PALU - Lukman, Heriyanto (JSTT, 2015)
The research aims to (1) describe pedagogical competence biology teacher at Madrasah Aliyah Negeri 2 Models of Palu. (2) describe the application of the scientific approach to the study of biology at Madrasah Aliyah Negeri 2 Models of Palu. This research is a descriptive study. Subjects in this study covers all biology teachers MAN 2 Model Palu is numbered 5 teachers. The type of data that is obtained is qualitative data. The results showed that the biology teacher pedagogical competence in every aspect, namely: understanding of the educational foundation of insight or good category; better understanding of the student category; developing curriculum or syllabus category good enough; learning good design category; implementation of learning that educates and dialogical either category; the use of learning technologies both categories; evaluation of the results of both categories; development of students to actualize various potentials both categories. MAN 2 Palu biology teacher in the application of scientific approaches, new can apply both on aspects observe and ask, but on aspects of collecting the data, associate or process information/reasoning, and communicate is still not good. Results of the data analysis portrait that teachers' understanding of biology is still lacking on the scientific approach as well as mastering the steps implementing aspects of the scientific approach.